RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PENCARIAN RUMAH KOST BERBASIS WEB DI DESA PENFUI TIMUR KABUPATEN KUPANG - Cyrillus Yuda Mardiyanto Pike; Mohamad Iqbal Ulumando; Risni Stefani (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
Advances in information technology offer opportunities to improve the efficiency of data management and information delivery, including in the area of ​​boarding house rentals. In Penfui Timur Village, Kupang Regency, the process of searching for and managing boarding houses is still carried out conventionally, making it less effective in providing fast and accurate information. This research aims to design and build a web-based boarding house search and management information system to facilitate access to information for prospective tenants and assist boarding house owners in managing data in a more structured manner. The method used is the waterfall software development model, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The system was developed using the PHP programming language and a MySQL database and can be accessed through a web browser. The results show that the system is capable of providing boarding house information quickly, structured, and easily accessible. Furthermore, the system helps boarding house owners manage data more effectively than manual methods. Based on testing results, all system features function properly, making this system a potential solution for improving the effectiveness of boarding house information management and delivery.